Rules and filters and their impact on success in chemical biology and drug discovery - Lipinski, Christopher (Henry Stewart Talks, 2014)
Academic targets and the translational gap, Chemistry & attrition (Reductionism, genomics and high throughput screening), Screening diverse compounds (advantages and disadvantages), Medicinal chemistry (A pattern recognition discipline), Biology and chemistry networks analysis, Ligand efficiency and selectivity